Application of martensitic SMA alloys as passive dampers of GFRP laminated composites - M. Bocciolone; M. Carnevale; A. Collina; N. Lecis; A. Lo Conte; B. Previtali; C.A. Biffi; P. Bassani; A. Tuissi (Fracture and Structural Integrity)
This paper describes the application of SMA (Shape Memory Alloy) materials to enhance the passive damping of GFRP (Glass Fiber Reinforced Plastic) laminated composite. The SMA has been embedded as reinforcement in the GFRP laminated composite and a SMA/GFRP hybrid composite has been obtained. Two SMA alloys have been studied as reinforcement and characterized by thermo-mechanical tests. The architecture of the hybrid composite has been numerically optimized in order to enhance the structural damping of the host GFRP laminated, without significant changes of the specific weight and of the flexural stiffness. The design and the resultant high damping material are interesting and will be useful in general for applications related to passive damping. The application to a new designed lateral horn of railway collector of the Italian high speed trains is discussed.